The Perceived Impact of COVID-19 on Functional Activities Among Canadian Education Workers: A Cross-Sectional Study - Serrano, Frances; Nowrouzi-Kia, Behdin; Oddson, Bruce; Bishai, Rita; Casole, Jennifer; Gohar, Basem (Frontiers in Public Health, 2022)
Objective: This cross-sectional study examined the self-perceived impact of the COVID-19 pandemic on 2378 education workers in Ontario, Canada, during the second wave. Methods: We examined six domains of functioning as per the short version of the World Health Organization Disability Assessment Schedule-2.0. Participants selected if their functioning had improved, remained unchanged or worsened during the pandemic for each item. Results: Educational workers described a general worsening of functional activities since the beginning of the pandemic. Moderate-to-extreme challenges were reported for all six functional domains. These challenges appeared to aggravate functional challenges for workers with disability, as indicated by pre-existing work accommodations. Older participants reported worse mobility than younger participants; however, they appeared to have better coping skills in learning new tasks and maintaining friendships. Women were more likely to report difficulties in maintaining household responsibilities. Conclusions: We consider the role of mental health challenges and pre-existing inequality as predictors of pandemic-related difficulties. Recommendations include more longitudinal research in this population and policymakers to incorporate a health promotion lens to support their education workers more proactively.